2020
DOI: 10.3390/su12239813
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biomimetics to Architectural and Urban Design: A Review across Scales

Abstract: Application of biomimetics has expanded progressively to other fields in recent years, including urban and architectural design, scaling up from materials to a larger scale. Besides its contribution to design and functionality through a long evolutionary process, the philosophy of biomimetics contributes to a sustainable society at the conceptual level. The aim of this review is to shed light on trends in the application of biomimetics to architectural and urban design, in order to identify potential issues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…This trend deserves further exploration with a larger and exhaustive sample. This trend converges with the increase in biomimicry research applied to architecture and urban design in the last years already demonstrated by previous research [ 4 , 5 ]. Two important milestones in the French timeline that contributed to more visibility and interest in biomimicry are the Alguesens project (2016) and the Ecotone project (2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This trend deserves further exploration with a larger and exhaustive sample. This trend converges with the increase in biomimicry research applied to architecture and urban design in the last years already demonstrated by previous research [ 4 , 5 ]. Two important milestones in the French timeline that contributed to more visibility and interest in biomimicry are the Alguesens project (2016) and the Ecotone project (2017).…”
Section: Discussionsupporting
confidence: 86%
“…Ecosystem-level biomimicry is a growing research topic [ 4 , 16 ], and its first position in our sample highlights a particular interest in the practice for this subject. We assume that ecosystem-level inspiration helps address transversal and systemic urban challenges such as biodiversity loss, the materials, and energy flows between urban and ecological systems [ 16 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several buildings have already employed this approach, going through formal biomimetic development methods for design, and integrating functional solutions to meet sustainable development challenges, as the Eastgate Building in Harare (Zimbabwe), and the Council House 2 (CH2) in Melbourne (Australia) [9,11]. At the urban scale, the application of biomimicry has been less explored [12]. Where it is apparent, design inspiration typically draws upon ecosystems rather than individual organisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several buildings have already employed this approach, going through formal biomimetic development methods for design, and integrating functional solutions to meet sustainable development challenges, as the Eastgate Building in Harare (Zimbabwe), and the Council House 2 (CH2) in Melbourne (Australia) [9,11]. At the urban scale, the application of biomimicry has been less explored [12]. Where it is apparent, design inspiration typically draws upon ecosystems rather than individual organisms [10].…”
Section: Introductionmentioning
confidence: 99%